(untitled) (Research in Agriculture Livestock and Fisheries, 2024)
Cocoa productivity is dependent on favourable weather variables. In Cameroon, climate change presents some phytosanitary challenges to cocoa farmers due to weed and cocoa pest problems. This paper analyzed the perceived phytosanitary impacts of climate change and the determinants of selected mitigation options in Cameroon. The data were collected using stratified random sampling from 303 farmers in Centre Cameroon. The data were analyzed with Probit regression. The results showed that cocoa farming operations were affected by climate change through weed control problems (51.48%), more incidence of black pod disease (65.02%), more incidence of malaria (68.98%), more cocoa pests (72.94%), death of cocoa trees (74.26%) and general reduction in cocoa yields (78.88%). The Probit regression results revealed that some adaptation methods were significantly influenced by perceived phytosanitary impacts of climate change such as perception of more pests, difficulties in weed control, death of cocoa trees, and black pod diseases. Other impacts such as malaria, pneumonia, lack of drinking water, inability to effective spray cocoa pod and dry the beans also showed some statistical significances with different impacts on adaptation. Cocoa farmers’ demographic characteristics such as education, gender, farming experience and primary occupation also influenced some adaptation methods. It was concluded that climate change presents significant constraints to cocoa production, and efforts to address the problem should integrate proper education on perception of the phytosanitary impacts and relevant mitigation with sensitivity on farmers’ gender, education level and the nature of primary occupation. Res. Agric. Livest. Fish. Vol. 11, No. 2, August 2024: 215-230